Making manufacturing cells work - Nyman, Lee R. (McGraw Hill, 1992)
This practical guide offers an effective, broad-based approach to flexible manufacturing cells (FMCs) planning and implementation, enabling plant managers and engineers to maximize FMC's ability to enhance product quality and reduce manufacturing time and inventory. Drawing from their own success in helping over 2,000 manufacturers to install FMCs, the authors illustrate the economic advantages of FMCs, show how to "sell" FMC to top brass and outline alternative FMCs to help users develop tailor-made cells. The book explains, step by step, how to design and install FMCs, upgrade FMCs using support systems and measure FMC's overall performance. It also provides an insight into future FMC trends, with the aid of case studies that highlight innovative strides in cellular manufacturing.